MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA FLIPBOOK PADA SISWA KELAS I SD NEGERI - Dumbela, Suci Rahmawati; Husain, Rusmin; Pulukadang, Wiwy Triyanty; Husain, Rustam I.; Monoarfa, Fidyawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The research question addressed in this research was: Can beginning reading skills in first-grade students of SDN 2 Telaga, Gorontalo Regency, be improved through the use of flipbook media? This research aims to improve beginning reading skills using flipbook media for the first-grade students at SDN 2 Telaga. This research was classroom action research. Data were collected through tests, observations, and documentation. Initial observation revealed that out of 19 students, 15 students (79%) demonstrated poor beginning reading skills. Improvement was observed over the implementation of classroom actions through two meetings in Cycle I and two meetings in Cycle II. In the first meeting of Cycle I, only 6 out of 19 students (32%) showed improvement in beginning reading. In the second meeting of Cycle I, this number increased to 10 students (53%). In the first meeting of Cycle II, 13 students (68%) showed improvement, and by the second meeting of Cycle II, 16 students (84%) had achieved good and accurate beginning reading skills. The findings indicate that the use of flipbook media significantly enhances beginning reading abilities in first-grade students at SDN 2 Telaga, Gorontalo Regency. ABSTRAKPenelitian ini dilaksanakan untuk meningkatkan keterampilan membaca permulaan pada siswa kelas I SDN 2 Telaga, Kabupaten Gorontalo, melalui penggunaan media pembelajaran flipbook. Penelitian ini menggunakan pendekatan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, dengan setiap siklus terdiri dari dua pertemuan. Teknik pengumpulan data meliputi tes hasil belajar, observasi aktivitas siswa, dan dokumentasi selama proses pembelajaran berlangsung. Berdasarkan observasi awal, diketahui bahwa dari 19 siswa, hanya 4 siswa (21%) yang menunjukkan kemampuan membaca awal, sementara 15 siswa (79%) belum menguasai keterampilan tersebut. Pelaksanaan tindakan menunjukkan adanya peningkatan yang signifikan. Pada siklus I pertemuan pertama, jumlah siswa yang mampu membaca meningkat menjadi 6 orang (32%). Pada pertemuan kedua siklus I, meningkat lagi menjadi 10 siswa (53%). Selanjutnya, pada siklus II pertemuan pertama terdapat 13 siswa (68%) yang mampu membaca dengan baik, dan pada pertemuan kedua meningkat menjadi 16 siswa (84%). Hasil ini menunjukkan bahwa penggunaan media flipbook efektif dalam meningkatkan kemampuan membaca permulaan.